1993
DOI: 10.1097/00000658-199305010-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Staged Celiotomy for Trauma Issues in Unpacking and Reconstruction

Abstract: 1. Reconstruction should occur after temperature, coagulopathy, and acidosis are corrected, usually within 36 hours after the damage control procedure. 2. Emergent reoperation should occur in any normothermic patient with unabated bleeding (greater than 2 U packed cells/hr). 3. ACS occurs in 15% of patients and is characterized by high peak inspiratory pressure, CO2 retention, and oliguria. Lethal reperfusion syndrome is common but preventable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
161
0
10

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(172 citation statements)
references
References 25 publications
0
161
0
10
Order By: Relevance
“…51,52 When taken as a whole, these indicators (pH, base deficit, core temperature) clearly reflect the extreme biochemical and physiologic stress that characterizes many of our most critically ill patients. Closing abdomens in patients manifesting physiologic extremis often leads to ACS, as first demonstrated by Morris and colleagues 53 in 1993. With fascial closure, the authors described severe abdominal distension in concert with raised peak airway pressures, CO 2 retention and oliguria.…”
Section: Abdominal Compartment Syndromementioning
confidence: 90%
See 1 more Smart Citation
“…51,52 When taken as a whole, these indicators (pH, base deficit, core temperature) clearly reflect the extreme biochemical and physiologic stress that characterizes many of our most critically ill patients. Closing abdomens in patients manifesting physiologic extremis often leads to ACS, as first demonstrated by Morris and colleagues 53 in 1993. With fascial closure, the authors described severe abdominal distension in concert with raised peak airway pressures, CO 2 retention and oliguria.…”
Section: Abdominal Compartment Syndromementioning
confidence: 90%
“…With fascial closure, the authors described severe abdominal distension in concert with raised peak airway pressures, CO 2 retention and oliguria. 53 The 63% mortality associated with subsequent reperfusion injury (i.e., after removing sponges from the intraperitoneal cavity during the second operation) that they observed was dramatic and also emphasized the importance of preventing "recurrent" or "tertiary" ACS. 54 In summary, these publications indicate that maintaining an open abdomen via a temporary abdominal closure, and therefore planning a delayed fascial closure, is not only a vital component of DCR, but is also a clear method for preventing ACS.…”
Section: Abdominal Compartment Syndromementioning
confidence: 98%
“…A core temperature of 348C is a critical point at which a significant alteration in platelet physiology occurs in trauma patients and at which enzyme activity decreases. Hypothermia is directly correlated to injury severity and an independent risk factor for mortality, reaching 100 per cent when core temperature is less than 328C in patients undergoing a laparotomy [34,35]. Hypothermia leads to a-adrenergic stimulation with vasoconstriction, exacerbating any organ hypoperfusion which may be already present secondary to hypotension from the injury.…”
Section: Volume Resuscitation In Major Traumamentioning
confidence: 99%
“…Morris et al had suggested that the reperfusion injury following abdominal decompression is a significant contributor to mortality in ACS patients (69). …”
Section: Intra-abdominal Pressurementioning
confidence: 99%
“…This pattern has been observed in several other models of compartment syndrome (CS), particularly that in the extremities. In acute limb CS, fasciotomy to release the compartment pressure often results in a severe reperfusion injury (78) which can be more substantial than the ischemic insult (69).…”
Section: From Iah To Acsmentioning
confidence: 99%